The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.compositesb.2016.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy and failure parameters in composite structures via a Component-Wise approach

Abstract: This paper deals with the static analysis of fiber reinforced composites via the Component-Wise approach (CW). The main aim of this work is the investigation of the CW capabilities for the evaluation of integral quantities such as the strain energy, or integral failure indexes. Such quantities are evaluated in the global structures and local volumes. The integral failure indexes, in particular, are proposed as alternatives to pointwise failure indexes. The CW approach has been recently developed as an extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Subsequently, exploiting CW capabilities, Maiarú et al. 31 extended 1D CUF-LE model for the prediction of failure parameters. Kaleel et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, exploiting CW capabilities, Maiarú et al. 31 extended 1D CUF-LE model for the prediction of failure parameters. Kaleel et al.…”
Section: Introductionmentioning
confidence: 99%
“…only fiber-matrix constituents. Subsequently, exploiting CW capabilities, Maiaru´et al 31 extended 1D CUF-LE model for the prediction of failure parameters. Kaleel et al 32 developed a novel and computationally efficient micromechanics framework based on 1D CUF-LE model to model components within RVEs.…”
Section: Introductionmentioning
confidence: 99%
“…The refined beam models are based on Carrera Unified Formulation (CUF), a hierarchical formulation which offers a procedure to obtain refined structural theories that account for variable kinematic description [25]. In particular, Component-Wise approach (CW) is adopted for modeling micromechanics problem, where various components of the RVE are modeled via 1D finite elements [26,27]. CW models adopt Lagrange type polynomial to define the cross-section of the beam.…”
Section: Introductionmentioning
confidence: 99%
“…Refined beam models are based on the Carrera Unified Formulation (CUF) [24], a hierarchical formulation to obtain refined structural theories that account for a variable kinematic description. In particular, the Component-Wise approach (CW) is adopted for modeling micromechanics problem, in which various components of the RVE are modeled via 1D finite elements [25,26]. CUF models can deal with arbitrary cross-sections, various classes of material models and boundary conditions, without any ad-hoc assumptions, which makes it an ideal candidate for micromechanics analysis.…”
mentioning
confidence: 99%
“…The efficiency of the framework is derived from the ability of CUF models to provide accurate 3D displacement and stress fields at a reduced computational cost (approximately one order of magnitude of degrees of freedom less as compared to standard 3D brick elements) [24,25,27]. Over the last couple of decades, CUF models have been extensively used for wide range of structural simulations such as static analysis of laminated beams [28], dynamic response for aerospace structures [29], vibration characteristics of rotating structures [30], evaluation of failure indices in composite structures [26], buckling and post-buckling analysis of compact and composite structures [31,32]. Carrera et al reported an extended review of recent developments in refined theories for beam based on CUF with particular focus on diverse applications [33].…”
mentioning
confidence: 99%